Understanding Heterogeneity in Contract Farming Among Indonesian Sugarcane Farmers - Hakim, Rizqi Imaduddin; Suprehatin; Rifin, Amzul (School of Business, Bogor Agricultural University (SB-IPB), 2024)
The transformation of the agricultural value chain on the production side is illustrated by the increased engagement of small-scale farmers facilitated by agribusiness firms through contract farming agreements. It is believed that the varied ramifications of contract farming are influenced not solely by contextual and implementation disparities but also by variations in the attributes of participating farmers. The dataset utilized in this investigation was sourced from the 2014 Indonesian Household Plantation Survey, comprising information from 8816 sugarcane farmers. Principal component analysis and cluster analysis were employed to categorize sugarcane farmers statistically and scrutinize the structure of sugarcane contract farming in Indonesia. Findings unveiled four distinct clusters of sugarcane farmers with discernible and significant dissimilarities in attributes. Contract farming is predominantly characterized by adult farmers with moderately sized self-owned land managed intensively and relatively favorable institutional access. Conversely, non-contract farming consists of adult farmers with small self-owned land working non-intensively and having limited institutional access. Keywords: cluster analysis, contract farming, principal component analysis, sugarcane